Study on surface retrogression and re-aging (SRRA) behaviour of aluminium alloy 7075 - Nozmi, Nor Azrin (2013)
Aluminum alloy 7075 is a very high strength material and have a wide range application throughout automotive, aircraft and aerospace industries, which possesses good mechanical properties with a combination of high strength, low density, ductility, and moderate toughness but often disposed to corrosion attack especially stress-corrosion cracking (SCC). The effects of the mechanical properties and stress corrosion cracking behavior were investigated to aluminium alloy 7075 when introduce to surface-retrogression and re-aging (SRRA) heat treatment and compared with T6, T73 and retrogression and re-aging (RRA) results. The method starts with carrying out solution heat treatment at 470°C for 1 hour. The samples were then quenched and followed by ageing process at 120°C from Oh to 24 hours ageing time. The 7075-T6 was obtained at this stage while 7075-T73 acquired after over-aged at l 70°C for 8 hours. The samples were exposed to heat temperature at 160°C, 180°C and 200°C, at holding time 5 and 25 minutes respectively, which produced RRA treated samples. At the same temperature and holding time as RRA, the samples were then introduced to oil on the surface of each specimen to produce the SRRA samples. After all, the RRA and SRRA samples were exposed to re-aging process at 120°C for 24 hours. Evaluation was based on mechanical properties, microsuucture evaluation and corrosion test. It was found that the hardness value for SRRA (from 86. 7 - 70. 7HRB) progressively reduced as the temperature and holding time increased if compared to T6 (88.8 HRB), but the strength of SRRA-treated (around 602.44 N/mrn2 - 658.52 N/mm2) was similar to T6 (651.53 N/mm2) but much higher than T73 (541.56 N/mm2) temper. As for the microstructure evaluation of SRRA, the precipitation of 11' phase inside the grains broaden and become denser as the temperature increase. The 11 ' of SRRA became thicker as the temperature and time increased if compared to RRA. This finding suggests that the long retrogression time at higher retrogression temperature cause the hardness value decrease due to 11' and 11 phases coarsening. It was found that the corrosion rate value of SRRA-treated without load is 0.0196 mm/yr and decrease to 0.0031 mm/yr when applied load. This result can be related to the crack occurrence at grain boundaries once the load was applied and encourage the corrosion to penetrate and grow at the grain boundaries. This is significant to the strength of the specimen where the strength of RRA and SRRA-treated is lower in this state as compared to the T6. The findings suggest that study for SRRA rotat1on speed can be conducted because it may be influenced to the microstructural stability since the heating of the alloy only be held at the surface and additional testing is recommended using Finite Element Method (FEM) in order to determine the behavior of SCC